Efficacy of Several Types of Pest Bird Deterrents and General Trend of Pest Birds at an Industrial Factory - Imran Mohd Hornain; Nik Fadzly N Rosely (Tropical Life Sciences Research, 2025)
Controlling pest birds is a complex problem, especially for large areas, compared to individual homes. This study presents a new perspective on pest birds plaguing a large semiconductor factory. We evaluated the efficacy of nine bird deterrent methods: alarm and distress calls broadcasted from portable speaker, sound frequencies ranged from (i) 24.5 kHz–45.5 kHz; and (ii) 13.5 kHz–45.5 kHz together with flashing lights emitted from sonic device, methyl anthranilate (MA), moving and static bird predator models, reflective compact discs, high and low visibility reflective tapes in deterring Barn Swallow (Hirundo rustica), Pacific Swallow (Hirundo tahitica) and Asian Glossy Starling (Aplonis panayensis) from perching on targeted spots. Monthly counts of pest birds roosting at study site were also conducted. Our results showed that alarm and distress calls broadcasted from portable speaker, sound frequencies ranged from 13.5 kHz–45.5 kHz together with flashing lights emitted from sonic device, moving and static bird predator model, reflective compact discs, high and low visibility reflective tapes were significantly effective in deterring pest birds from targeted spots. The pest bird population reached its peak (35,063) in January 2021, while the least (3,685) was recorded in May 2021. The effectiveness of pest bird deterrents might be influenced by the quantity and method of deployment.